Challenge based on STEM-Context Learning Assisted by Role Playing Game: Analysis of Creative Thinking Skills on Self-Efficacy - Laily Arfina Sari; Adi Satrio Ardiansyah; Ida Zubaidah (Jurnal Inovasi Matematika, 2026)
Creative thinking skills are essential skills that students need to possess in the 21st century. In reality, creative thinking skills of Indonesian students remain low. This is evidenced by the 2022 PISA results, in which Indonesia only scored 19 out of 60. This research aims to analyze the effectiveness of Challenge based on STEM-Context Learning assisted by RPG, analyze the influence of self-efficacy on creative thinking skills, and describe creative thinking skills in terms of self-efficacy. This research employed a mixed-method approach with a sequential explanatory design. The population of this study consisted of eighth-grade students at SMPN 41 Semarang. The research sample was class VIII B and VIII G which were selected through simple random sampling. The research subjects were six students were selected using a purposive sampling, consisting of two students from each self-efficacy category. The results revealed that Challenge based on STEM-Context Learning effectively improved creative thinking skills, and self-efficacy influenced on creative thinking skills by 47.7%. Based on the description of creative thinking skills in terms of self-efficacy, it was found that students with high self-efficacy were able to meet the indicators of fluency, flexibility, and novelty; students with moderate self-efficacy were only able to meet the indicators of fluency and flexibility; while students with low self-efficacy did not meet the indicators of fluency, flexibility, and novelty.